2007
DOI: 10.1097/qai.0b013e31805c9d52
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Subtherapeutic Plasma Concentrations of Efavirenz in Children

Abstract: Our findings, together with those of previous studies, indicate that many children dosed according to the current guidelines do not achieve adequate efavirenz exposure. Because low efavirenz concentrations are associated with the rapid emergence of efavirenz-resistant mutations and treatment failure, the current recommended efavirenz doses should be re-evaluated, especially in developing countries, where therapeutic drug monitoring is seldom available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
52
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 12 publications
6
52
1
1
Order By: Relevance
“…(i) C min s, C max s, and AUCs were consistent with those of previous studies: 1.64 mg/liter, 3.71 mg/liter, and 65.2 mg/ liter ⅐ h, respectively, in our study compared to 1.18 to 1.45 mg/liter, 4.09 to 5.52 mg/liter, and 60 to 63.6 mg/liter ⅐ h in previous studies (7,16,19) (Table 3).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…(i) C min s, C max s, and AUCs were consistent with those of previous studies: 1.64 mg/liter, 3.71 mg/liter, and 65.2 mg/ liter ⅐ h, respectively, in our study compared to 1.18 to 1.45 mg/liter, 4.09 to 5.52 mg/liter, and 60 to 63.6 mg/liter ⅐ h in previous studies (7,16,19) (Table 3).…”
Section: Discussionsupporting
confidence: 81%
“…Theoretically, C min may be more important to provide continuous suppression of viral replication; thus, we considered C min the target pharmacokinetic parameter in our study. In all studies, a high percentage of children fell below the target concentrations (7,16,19,21). Similarly, with the recommended dose of EFV administered to 46 out of 48 children in the present study, 19% of children had C min s of Ͻ1 mg/liter.…”
Section: Discussionmentioning
confidence: 83%
“…Likewise, previous studies have estimated the relative bioavailability of the oral liquid formulations in children to be 0.47 and 0.62 (48,49). Such low bioavailability may explain the high incidence of subtherapeutic EFV concentrations among children (17)(18)(19) and suggests the need to use oral liquid formulations at doses that are 150% of the capsule doses.…”
Section: Discussionmentioning
confidence: 99%
“…Little information is available about the correlation between EFV PK parameters and pediatric population covariates and the influence of developmental changes that take place during infancy and childhood on CYP2B6 expression and EFV PK (16). Moreover, some clinical studies have reported a high prevalence of subtherapeutic EFV concentrations among children, suggesting a need to develop alternative dosing guidelines for this important population (17)(18)(19). The aims of the current study were to quantify the interindividual and intraindividual variability of EFV PK in HIV-1-infected children; to identify factors that describe this variability, including growth and maturation; and to develop a population pharmacokinetic model that incorporates these covariates in order to guide EFV dosing in children.…”
mentioning
confidence: 99%
“…Marzolini and co-workers proposed a 1000-4000 g/L plasma range at mid-dosing interval as a suitable target for EFV drug levels [2]. When EFV levels reach toxic levels (>4000 g/L) a higher incidence of side-effects occurs such as insomnia, dizziness, abnormal dreams and loss of concentration [2,3], while subtherapeutic levels (<1000 g/L) can lead to treatment failure due to viral resistance [4,5]. It is thus important to ensure that EFV plasma levels are within the therapeutic window.…”
Section: Introductionmentioning
confidence: 99%